The Impact of Learning Loss During a Pandemic Among Students - Yuliyanto, Riyan; Deviyanti Yamin, Rafista (JASSP, 2022)
Online learning conducted during the pandemic is a solution to this global disaster dilemma. Students must follow government policies to carry out online learning amid their limitations. Even though technology is currently developing rapidly, there are still difficulties that cause learning at home to be not optimal. The existence of difficulties in the learning process will result in learning loss. This study aims to see the impact of learning loss experienced by students. This study uses a literature study method by describing the findings from various literature sources from previous research. The results of this study indicate that the form of learning loss experienced by students will cause lost for years and have an impact on academic performance until they become adults cumulatively. Students feel a decrease in interest in learning compared to face-to-face learning. To address learning loss, policymakers should consider targeted programs, use teaching methods, improve teacher-student communication and involve parents to accelerate recovery and minimize the impact of learning loss.